The Moderating Effect of Honesty on Tax Noncompliance Behavior - Md Radzi, Nor Zuhairatun (International Information Institute, 2016)
Tax noncompliance issues remain debated and the puzzle unsolved.The percentage of noncompliance is still increasing since Malaysia implemented Self- Assessment System (SAS) in 2004 towards individual taxpayers. Previous studies focused more on economic factors of noncompliance, therefore, this report intends to appear at the non economic factors. Theory of Virtue Ethics (TVE) used to explain the extended Theory of Planned Behavior (TPB) in examining the moderating effect of honesty in tax noncompliance behavior.